Military lives: coaching transitions. Issue 5 (5th June 2017) - Beech, Nick; Gold, Jeff; Beech, Susan
Abstract : Purpose: The purpose of this paper is to first consider how veterans use talk to shape interpretations of personal and social identify. Second, this paper seeks to gain an understanding of how veterans see themselves in a civilian world, their ability to re-conceptualise and realign their perspective on life to support their transition in to a civilian world. Design/methodology/approach: Underpinned by Ricoeur's theory of narrative identity, the work provides a qualitative analysis data from coaching interviews with five veterans. Findings: The findings revealed the on-going legacy of military life and how its distinctiveness and belief centred on kinship shapes personal identity and the way they see their civilian world. The work sheds light on to the benefits of this Ricoeur's self-reflexive approach and how it can be used to provide a deeper insight in to the nature of personal transitions and how narrative can be used to expose complexities of the narratives of personal history and meaning as the narrator becomes both the seeker and what is sought. Practical implications: The work reinforces the value of Ricoeur's self-reflexive approach identifying narrative mediating between two "poles" of identity and the act of mimesis; prefiguration, configuration and refiguration as veterans project stories of their world and their place within it. Originality/value: The paper provides new insights in to the importance of narrative identify broadening its potential application with engagement across diverse communities, thereby providing depth and rigour of its conceptual understanding of personal identify. The work further provides insights in to the challenges facing veterans to integrate within a civilian society.